Towards scalable and controlled synthesis of metal–organic framework materials using continuous flow reactors. Issue 4 (23rd June 2016) - Dunne, Peter W.; Lester, Edward; Walton, Richard I.
Abstract : Continuous flow synthesis offers potential for large-scale production of metal–organic frameworks with control of composition and microstructure for practical applications. Abstract : Metal–organic frameworks have emerged as one of the most diverse new families of materials in the past few years. Their hybrid structures, combinations of inorganic and organic moieties, give a wide range of complex architectures with resultant properties that are suitable for numerous important fields, including porosity for molecular sieving and sensing, heterogeneous catalysis, drug delivery, and energy storage. If applications of these materials are to be realised then scalable synthesis is required, taking laboratory batch reactions towards industrial production. Continuous flow reactors offer the most versatile method for scaling their solvothermal synthesis, with the largest range of materials accessible, in high yield, and with control over crystal form.